Estimating one's own and others' multiple intelligence: a cross-cultural study from Guinea Bissau and Portugal - Felix Neto (2009)
This study examined the estimations of multiple intelligences for self, partner and parents. One hundred and fifty two students (males = 81, females = 68, and 3 have not indicated their sex; mean age = 24.02, SD = 3.08) from Guinea Bissau estimated their own, their partners', and their parents' 10 scores on each of Gardner's ten multiple intelligences: verbal (linguistic), logical (mathematical), spatial, musical, body-kinesthetic, Interpersonal, Intrapersonal, existential, spiritual and naturalistic. In contrast to previous results (A. Furnham, 2001) sex differences in self-estimates did not occur In this Guinean sample. Participants rated overall intelligence of their father higher than that of their mother. An existing data set on estimates of intelligence in a Portuguese sample was used for a cross-cultural comparison between Portuguese and Guinean participants. There were consistent and clear culture differences. Guinean gave higher self, partner and family ratings than Portuguese. Results are discussed in terms of the growing literature in the self-estimates of intelligence, as well as limitations of that approach.